2005
DOI: 10.1093/ajcn/81.4.934
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of n–6 to n–3 fatty acids and bone mineral density in older adults: the Rancho Bernardo Study

Abstract: A higher ratio of n-6 to n-3 fatty acids is associated with lower BMD at the hip in both sexes. These findings suggest that the relative amounts of dietary polyunsaturated fatty acids may play a vital role in preserving skeletal integrity in older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
5
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 31 publications
(54 reference statements)
9
160
5
2
Order By: Relevance
“…Also, the intake of omega-6 fatty acids has been previously shown to be associated with a lower bone mineral density, and a high ratio of omega-6 to omega-3 has been reported to be detrimental for bone formation (Albertazzi and Coupland, 2002). In the Rancho Bernardo Study, after assessing bone mineral density in 1532 community-dwelling men and women aged 45-90 years, an increasing ratio of total dietary omega-6 to omega-3 fatty acids was significantly and independently associated with lower bone mineral density (Weiss et al, 2005). The results of the investigation conducted by Macdonald et al, (2004) also suggested that PUFAs are harmful to bone in women, but, to our knowledge, no previous epidemiologic study has reported a direct association between PUFA intake and a higher fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the intake of omega-6 fatty acids has been previously shown to be associated with a lower bone mineral density, and a high ratio of omega-6 to omega-3 has been reported to be detrimental for bone formation (Albertazzi and Coupland, 2002). In the Rancho Bernardo Study, after assessing bone mineral density in 1532 community-dwelling men and women aged 45-90 years, an increasing ratio of total dietary omega-6 to omega-3 fatty acids was significantly and independently associated with lower bone mineral density (Weiss et al, 2005). The results of the investigation conducted by Macdonald et al, (2004) also suggested that PUFAs are harmful to bone in women, but, to our knowledge, no previous epidemiologic study has reported a direct association between PUFA intake and a higher fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Total fat intake (Kato et al, 2000;Macdonald et al, 2004) and, more specifically, saturated fat intake (Corwin et al, 2006) have been reported to be associated with a higher risk of bone loss and osteoporotic fractures. However, a previous study conducted in a Mediterranean country has reported a beneficial role for monounsaturated fat (MUFA) (Trichopoulou et al, 1997), whereas some studies have also found associations between high polyunsaturated fatty acids (PUFA) intake and lower bone density (Macdonald et al, 2004;Weiss et al, 2005). We evaluated the association between fat intake, serum lipids and the risk of osteoporotic fractures using a case-control design.…”
Section: Introductionmentioning
confidence: 95%
“…In a definitive review by Kruger and Horrobin [8] it was suggested that PUFAs of the n-3 series, as well as the n-6 fatty acid gamma linolenic acid (GLA), may prove beneficial when consumed in appropriate amounts. In addition, it has been shown that a reduction of the n-6/n-3 PUFA ratio could result in increased bone strength in animals [9] and in humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] There is increasing evidence that lack of certain PUFAs in the diet can induce bone loss, [9][10][11] while dietary supplementation of some PUFAs has been shown to be beneficial for bone. 5,6,[12][13][14] Clinical studies have shown, for instance, that supplementation of calcium, g-linolenic acid (GLA) and eicosapentaenoic acid (EPA) in the diets of elderly women decreases bone turnover and increases bone mineral density.…”
Section: Introductionmentioning
confidence: 99%